Effectiveness of sedation in dacryocystorhinostomy surgery - Taludhar, S; Adhikari, S; Bhattarai, BK (Nepalese Journal of Ophthalmology, 2010)
Background: Chronic dacryocystitis is a common ophthalmic problem almost always requiring surgery as the only definitive treatment. Aim: To compare the perioperative outcome of external DCR surgery under local anesthesia with and without sedation. Subjects and methods: One hundred consecutive patients with chronic dacryocystitis undergoing dacryocystorhinostomy (DCR) surgery were randomly divided into two groups using computer generated random table. Group A underwent DCR under local anesthesia (LA) without sedation and group B under LA with sedation. The outcome parameters were intra-operative pain, surgeon's comfort, intra-operative complications and duration of surgery. Statistical analysis: SPSS version 11.5 software was used. Chi square test was used to compare the difference between the groups. Results: There were 50 patients in each group. The mean age ± SD of the patients was 34.4±12.12 years (95% CI=28.89-38.55 years). Sixty-nine percent of them were female. Significantly higher number of patients experienced pain in Group A as compared to Group B (100% vs 50%, P<0.001) Surgeon's discomfort was significantly present in group A as compared to group B (70% vs 10%), (p=0.00001). Blood loss was significantly more in group A than in group B (p=0.017). There was no significant difference in the duration of surgery. The post operative success rate in both the groups was comparable after six months of followup. Conclusion: The use of sedation with LA improves the perioperative outcome of DCR surgery in terms of patient's pain, surgeon's comfort and intra-operative complications. Key words: dacryocystitis; dacryocystorhinostomy; sedation DOI: 10.3126/nepjoph.v1i1.3670 Nep J Oph 2009;1(1):25-31